Growth of the Ectomycorrhizal Fungus Pisolithus Microcarpus in different nutritional conditions - Rossi,Márcio José (2011)
The most important plant species employed in reforestation programs depend on ectomycorrhizal fungi for their establishment and growth. The exploitation of this symbiosis to improve forest productivity requires fungal inoculants in a large scale level. To develop such a technology it is necessary to define the optimal composition of the culture medium for each fungus. With these objectives in mind, the effect of the composition of the culture medium on biomass production of the ectomycorrhizal fungus Pisolithus microcarpus (isolate UFSC-Pt116) was studied. The original composition of two culture media, already employed for cultivation of ectomycorrhizal fungi, was submitted to several variations with the C/N ratio as the main variable. A variation of the Pridham-Gottlieb medium was the most efficient for the production of biomass. Therefore, it was submitted to a factorial assay where glucose, peptone and yeast extract components were the factors analyzed. Results showed that the glucose concentration may be increased up to 40 % in order to promote higher biomass production. Peptone had a positive effect on this variable, whereas yeast extract promoted a deleterious effect. These results indicate that it is advisable to eliminate yeast extract from the medium and replace it with peptone prior to use.